Current epidemiological knowledge about the role of flavonoids in prostate carcinogenesis - Sak, K. (Experimental Oncology, 2017)
Numerous experimental studies have demonstrated anticancer action of polyphenolic plant metabolites. However, data about associations between dietary intake of plant-derived flavonoids and prostate cancer risk are still sparse and inconsistent. This minireview compiles the epidemiological findings published to date on the role of flavonoids in prostate tumorigenesis, discusses the reasons of inconsistencies and elicits the promising results for chemoprevention of this malignancy. Long-term consumption of high doses of soy isoflavones can be the reason of markedly lower clinically detectable prostate cancer incidence among Asian men compared to their counterparts in the Western world. The ability to metabolize daidzein to equol, the most biologically active isoflavone, by the certain intestinal bacteria also seems to contribute to this important health benefit. The increasing incidence rate of prostate cancer related to adoption of westernized lifestyle and dietary habits makes the issue of chemoprevention ever more important and directs the eyes to specific food components in the Eastern diet. If further large-scale epidemiological studies will confirm the protective effects of isoflavones against prostate cancer, this could provide an important way for prostate cancer prevention, as diet is a potentially modifiable factor in our behavioral pattern.